Tracing the First Voice: The Influence of Mother Tongue on Second Language Acquisition-A Study of English Learning among Undergraduate Students in Pakistani Universities - Muqaddar Zaka; Athar Abbas (Corresponding Author); Ayesha Tahir; Laila Sohail (`, 2025)
This study examines the cognitive, pedagogical, and sociological aspects of how the mother tongue affects undergraduate English language learners at Pakistani universities. The study examines how L1 helps or hinders English learning, including vocabulary understanding, grammar acquisition, pronunciation, and classroom confidence, using a quantitative survey of 60 students whose primary mother tongues are Urdu and Punjabi. The findings show that the mother language has two functions: it can interfere with pronunciation and provide a helpful linguistic foundation through shared structures, but it can also cause problems like direct translation errors. The study emphasizes a range of student perspectives impacted by environmental, linguistic, and individual factors, highlighting the significance of well-rounded teaching approaches that use the mother tongue to improve learning without sacrificing proficiency in English. Keywords: Mother tongue, Second Language Acquisition, Undergraduate students, Pronunciation, Fluency, Grammar